Frontiers of combining systems : 11th International Symposium, FroCoS 2017, Brasília, Brazil, September 27-29, 2017, Proceedings /: 11th International Symposium, FroCoS 2017, Brasília, Brazil, September 27-29, 2017, Proceedings. (2017) - Unknown
No abstract available